From the Altar (Dor) to the Church Pulpit: Transforming the Worship Values of the Klon Tribe in Christian Religious Education - Oci Cristy Darlinta Koilha (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study explores the transformation of traditional worship values within the Klon tribe community in Alor, East Nusa Tenggara. Prior to their conversion to Christianity, the community practiced a religious system centered on mesbah (stone altars) where they worshiped ancestral spirits and local deities. The introduction of Christianity through inculturation led to a significant shift in worship practices, transitioning from rituals at the mesbah to those at the church pulpit. However, rather than losing their spiritual and communal values, these traditions adapted and were integrated into Christian practices. The study highlights how elements of local wisdom were preserved and transformed, creating a bridge between indigenous beliefs and Christian teachings. This transformation demonstrates that the core values of worship such as reverence for ancestors and community solidarity continued to play a role in the newly adopted Christian practices. The findings of this study emphasize the importance of understanding such cultural transformations, especially in the context of Christian Religious Education. It suggests that contextualizing religious teachings within local traditions and wisdom can foster a deeper, more meaningful connection to faith for communities undergoing cultural change. By valuing these local traditions, Christian Religious Education can become more relevant and impactful, encouraging a harmonious blending of old and new beliefs.